PENGARUH PENERAPAN E-REGISTRATION, E-FILING DAN E-BILLING TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA MALANG 2021 - Safitri Safitri; Nur Diana; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
The effect of the application of e-registration, e-filing and e-billing on individual taxpayer compliance in Malang City 2021. The aims of this study are: 1. To determine the effect of e-registration implementation on taxpayer compliance in Malang City. 2. To determine the effect of the implementation of e-filing on taxpayer compliance in the city of Malang. 3. To determine the effect of the implementation of e-billing on taxpayer compliance in the city of Malang. 4. To determine the effect of applying e-registration, e-filing and e-billing simultaneously has a significant effect on individual taxpayer compliance in Malang City. The data collection method applies a questionnaire and the data analysis method applied in this study is descriptive statistical analysis, research instruments, normality, classical assumptions, multiple linear regression analysis, and hypotheses. From the results obtained by the researcher, it can be proven that there is an influence of the variables e-registration, e-filing and e-billing which both have a significant effect both simultaneously and partially on taxpayer compliance in the city of Malang.Keywords: e-registration, e-filing, e-billing and individual taxpayer compliance